2017
DOI: 10.1128/mcb.00139-17
|View full text |Cite
|
Sign up to set email alerts
|

Gle1 Regulates RNA Binding of the DEAD-Box Helicase Ded1 in Its Complex Role in Translation Initiation

Abstract: DEAD-box proteins (DBPs) are required in gene expression to facilitate changes to ribonucleoprotein complexes, but the cellular mechanisms and regulation of DBPs are not fully defined. Gle1 is a multifunctional regulator of DBPs with roles in mRNA export and translation. In translation, Gle1 modulates Ded1, a DBP required for initiation. However, overexpression causes defects, suggesting that Ded1 can promote or repress translation in different contexts. Here we show that expression suppresses the repressive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 50 publications
6
45
0
Order By: Relevance
“…cerevisiae [ 17 ]. Moreover, Gle1 regulates RNA binding of the DEAD-box helicase Ded1 in translation initiation[ 18 , 19 ]. Recently, it was also demonstrated that the localization of GLE1 in the centrosome plays a role in centrosome integrity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae [ 17 ]. Moreover, Gle1 regulates RNA binding of the DEAD-box helicase Ded1 in translation initiation[ 18 , 19 ]. Recently, it was also demonstrated that the localization of GLE1 in the centrosome plays a role in centrosome integrity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to regulating Dbp5 at the NPC, Gle1 is required for the function of distinct Dbps at non-NPC subcellular locales. In S. cerevisiae , Gle1-IP 6 regulates Dbp5 activity during translation termination, and Gle1 impacts the ATPase activity and RNA binding of Ded1, another DEAD-box protein, for efficient translation initiation independently of IP 6 1215 . In humans, hGle1 shuttles between the nucleus and cytoplasm with at least two isoforms, hGle1A and hGle1B, produced from a single gene 11,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Ded1p acts as an RNA-dependent helicase or ‘RNA chaperone’ and can remodel mRNP complexes. Ded1p can function as a translational repressor when present at high concentrations; its overproduction impairs yeast cell growth and induces the assembly of P-bodies or SGs [63,295]. To examine Ded1p localization in 15 min of glucose starvation, plasmids encoding Ded1p-GFP and Pub1p-mCherry were transformed into WT yeast and the fluorescence signals tested for co-localization against the non-starved cells.…”
Section: Formation Of Cytoplasmic Foci and The Fate Of Inhibited Mrnamentioning
confidence: 99%